2012
DOI: 10.1097/brs.0b013e318231493c
|View full text |Cite
|
Sign up to set email alerts
|

Body Appearance and Quality of Life in Adult Patients With Adolescent Idiopathic Scoliosis Treated With a Brace or Under Observation Alone During Adolescence

Abstract: Patients who experienced less body asymmetry were more satisfied with treatment and had a better quality of life. In spite of similar curve sizes and trunk rotation in both groups, the nonbraced patients felt that their body appearance was less distorted than that of the braced patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
0
46
1
Order By: Relevance
“…"^' Carreon et aP° compared preoperative to 1 year postoperative SRS-22 values in a cohort of patients with AIS (mean age = 14 [10][11][12][13][14][15][16][17][18]) and determined significant MCID values to be 0.20,0.08, and 0.98 for the pain, activity, and self-image domains, respectively ( Table 2). Radiographical measures collected included T2-T12, T5-T12, and greatest Cobb kyphosis, major coronal Cobb angle, C7 sagittal vertical axis, lordosis, and thoracic and lumbar apex location and translations.…”
Section: Methodsmentioning
confidence: 99%
“…"^' Carreon et aP° compared preoperative to 1 year postoperative SRS-22 values in a cohort of patients with AIS (mean age = 14 [10][11][12][13][14][15][16][17][18]) and determined significant MCID values to be 0.20,0.08, and 0.98 for the pain, activity, and self-image domains, respectively ( Table 2). Radiographical measures collected included T2-T12, T5-T12, and greatest Cobb kyphosis, major coronal Cobb angle, C7 sagittal vertical axis, lordosis, and thoracic and lumbar apex location and translations.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of scoliosis is determined from the Cobb angle, visualised in an anterior-posterior x-ray, and this is probably the most decisive factor when determining the treatment strategy. However, appearance can also influence the decision to opt for surgical treatment (1,(5)(6) : the majority of patients are concerned about their body before, during and after treatment, although to a varying extent depending on the individual, and this anxiety may affect their general well-being (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The largest of the previous observational studies in adults, who in adolescence were braced or treated surgically or observed, included 1476 patients and 1755 controls [12], while other major studies included 145 surgically treated, 127 braced, and 100 control subjects [4] and 40 observed and 37 braced patients [13]. Response rates in those, and other studies, described by Goldberg et al [12], ranged from 48% to 89%.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery or brace treatment may also lead to psychological side effects [3, 4, 8, 9]. Long-term outcome reports [10], including the Iowa [11], Montreal [12], and Göteborg [4, 13] series, suggested that deformity causes psychopathological effects or demonstrated positive coping mechanisms [3, 12]. Furthermore, the available papers focus on the assessment of health-related quality of life and utilize generic (typically the SF-36 or WHOQOLBREF questionnaires) or condition-specific (e.g., the Scoliosis Research Society (SRS)-22 questionnaire) measures with their physical, social, and emotional roles, mental functioning, bodily pain, and body image components, incorporated to produce a measure of a person's perceived general health status [5, 7].…”
Section: Introductionmentioning
confidence: 99%